Repeated sprint training under hypoxia improves aerobic performance and repeated sprint ability by enhancing muscle deoxygenation and markers of angiogenesis in rugby sevens - Pramkratok, W.; Songsupap, T.; Yimlamai, T. (European Journal of Applied Physiology, 2022)
Objective To evaluate the effects of repeated sprint (RS) training in hypoxia on aerobic performance, repeated sprint ability (RSA), and muscle oxygenation in Rugby Sevens.